Focusing a round coherent beam by spatial filtering the horizontal source. (20th October 2020) - Dufresne, Eric M.; Narayanan, Suresh; Reininger, Ruben; Sandy, Alec R.; Lurio, Larry
Abstract : The use of spatial filtering with a horizontal slit near the source to enlarge the horizontal coherence in an experimental station and produce a diffraction‐limited round focus at an insertion device beamline for X‐ray photon correlation spectroscopy experiments is illustrated. This scheme has now been in use since 2019 for the 8‐ID beamline at the Advanced Photon Source, sharing the undulator beam with two separate beamlines, 8‐ID‐E and 8‐ID‐I at 7.35 keV, with increased partially coherent flux, reduced horizontal spot sizes on samples, and good speckle contrast. Abstract : This paper illustrates the use of spatial filtering with a horizontal slit near the source to enlarge the horizontal coherence in an experimental station and produce a diffraction‐limited round focus at an insertion device beamline for X‐ray photon correlation spectroscopy experiments. Simple expressions are provided to guide the optical layout, and wave propagation simulations confirm their applicability. The two‐dimensional focusing performance of Be compound refractive lenses to produce a round diffraction‐limited focus at 11 keV capable of generating a high‐contrast speckle pattern of an aerogel sample is demonstrated. The coherent scattering patterns have comparable speckle sizes in both horizontal and vertical directions. The focal spot sizes are consistent with hybrid ray‐tracing calculations. Producing a two‐dimensional focus on the sample can be helpful to resolve speckle patterns with modern pixel array detectors with high visibility. This scheme has now been in use since 2019 for the 8‐ID beamline at the Advanced Photon Source, sharing the undulator beam with two separate beamlines, 8‐ID‐E and 8‐ID‐I at 7.35 keV, with increased partially coherent flux, reduced horizontal spot sizes on samples, and good speckle contrast.